Confessioni e comunità religiose nell’Europa dell’Est, pluralismo religioso e politiche legislative degli Stati (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: Sistemi di classificazione dei rapporti e individuazione degli interlocutori istituzionali delle confessioni religiose - 2. Il “laboratorio” dell’Europa dell’Est come luogo di sperimentazione del pluralismo intra confessionale - 3. La gestione delle relazioni tra Stato e confessioni religiose attraverso gli uffici - 4. I problemi nuovi posti dal moltiplicarsi delle confessioni nei diversi paesi europei - 4.1. L’area baltica - 4.2. (segue) Le Repubbliche russofone - 4.3. (segue) Le Repubbliche dell’Europa Centrale - 4.4. (segue) I Balcani Orientali - 4.5. (segue) I territori della ex Repubblica Jugoslava - 4.6. (segue) Le scelte differenziate delle Repubbliche ex jugoslave in materia di Rapporti tra Stato e confessioni religiose - 5. La felice anomalia albanese - 6. Un contributo all’elaborazione di linee guida ai rapporti tra Stato e confessioni religiose in Europa.Confessions and religious communities in Eastern Europe, religious pluralism and legislative policies of the StatesABSTRACT: The intervention reconstructs the supporting lines of the activity of the national office of each legal system in charge with the maintenance of the relations between the State and the confessions and religious communities in the Eastern European countries. Through this perspective, the ecclesiastical politics of 19 countries is reconstructed, highlighting the genesis and the peculiar characteristics of their legislations and highlighting the underlying lines that are at the root of the choices of their systems. Particular attention is dedicated to the definition of the different models to which the States refer in relation to their effectiveness in maintaining religious peace while respecting the principle of equality and freedom among the various religious confessions. The article aims to be a contribution to the development of guidelines for relations between the state and religious confessions in Europe.